2012
DOI: 10.1155/2012/235646
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Feedback following Participation in a Family-Based Intervention for Youth Mental Health

Abstract: Background. This paper presents findings derived from consumer feedback, following a multicentre randomised controlled trial for adolescent mental health problems and substance misuse. The paper focuses on the implementation of a family-based intervention, including fidelity of delivery, family members' experiences, and their suggestions for program improvements. Methods. Qualitative and quantitative data (n = 21) were drawn from the Deakin Family Options trial consumer focus groups, which occurred six months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Overall these findings provide initial, albeit limited, support for this type of family based intervention as a potentially efficacious model for improving parent anxiety and attachment in parents of youth with high prevalence mental health conditions. Qualitative information gathered from parents in a post intervention focus group supported the preliminary quantitative findings of this study [13], relating to decreased parent stress and increased perceived coping in parents. Given the literature relating to high rates of stress and burnout in parents and carers, this study provides an important initial contribution as a potentially beneficial treatment for anxious parents of depressed, anxious and substance misusing youth.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Overall these findings provide initial, albeit limited, support for this type of family based intervention as a potentially efficacious model for improving parent anxiety and attachment in parents of youth with high prevalence mental health conditions. Qualitative information gathered from parents in a post intervention focus group supported the preliminary quantitative findings of this study [13], relating to decreased parent stress and increased perceived coping in parents. Given the literature relating to high rates of stress and burnout in parents and carers, this study provides an important initial contribution as a potentially beneficial treatment for anxious parents of depressed, anxious and substance misusing youth.…”
Section: Discussionsupporting
confidence: 61%
“…Parents in the BEST Plus treatment discussed their difficulties with other parents experiencing similar issues, and in doing so, normalized their experiences. Qualitative information obtained from a consumer reference group held at the end of the project [13] suggested that the BEST Plus program had achieved this goal of offering a supportive environment, likely to alleviate parental anxiety symptoms. For example, participants reported enjoying the collegial atmosphere of the BEST Plus group, contributing their experiences to help others in the group, and receiving advice, understanding and support from other members.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations